Kim Ki-duk - Chung, Hye Seung, 1971- (Book collections on Project MUSE., 2012)
This study investigates the controversial motion pictures written and directed by the independent filmmaker Kim Ki-duk, one of the most acclaimed Korean auteurs in the English-speaking world. Propelled by underdog protagonists who can only communicate through shared corporeal pain and extreme violence, Kim's graphic films have been classified by Western audiences as belonging to sensationalist East Asian "extreme" cinema, and Kim has been labelled a "psychopath" and "misogynist" in South Korea. Drawing upon both Korean-language and English-language sources, Hye Seung Chung challenges these misunderstandings, recuperating Kim's oeuvre as a therapeutic, yet brutal cinema of Nietzschean ressentiment (political anger and resentment deriving from subordination and oppression)